Adiposity, metabolites, and colorectal cancer risk: Mendelian randomization study - Bull, Caroline J; Bell, Joshua A; Murphy, Neil; Sanderson, Eleanor; Davey Smith, George; Timpson, Nicholas J; Banbury, Barbara L; Albanes, Demetrius; Berndt, Sonja I; Bézieau, Stéphane; Bishop, D Timothy; Brenner, Hermann; et al. (BMC medicine, 2020)
BACKGROUND: Higher adiposity increases the risk of colorectal cancer (CRC), but whether this relationship varies by anatomical sub-site or by sex is unclear. Further, the metabolic alterations mediating the effects of adiposity on CRC are not fully understood. METHODS: We examined sex- and site-specific associations of adiposity with CRC risk and whether adiposity-associated metabolites explain the associations of adiposity with CRC. Genetic variants from genome-wide association studies of body mass index (BMI) and waist-to-hip ratio (WHR, unadjusted for BMI; N = 806,810), and 123 metabolites from targeted nuclear magnetic resonance metabolomics (N = 24,925), were used as instruments. Sex-combined and sex-specific Mendelian randomization (MR) was conducted for BMI and WHR with CRC risk (58,221 cases and 67,694 controls in the Genetics and Epidemiology of Colorectal Cancer Consortium, Colorectal Cancer Transdisciplinary Study, and Colon Cancer Family Registry). Sex-combined MR was conducted for BMI and WHR with metabolites, for metabolites with CRC, and for BMI and WHR with CRC adjusted for metabolite classes in multivariable models. RESULTS: In sex-specific MR analyses, higher BMI (per 4.2 kg/m2) was associated with 1.23 (95% confidence interval (CI) = 1.08, 1.38) times higher CRC odds among men (inverse-variance-weighted (IVW) model); among women, higher BMI (per 5.2 kg/m2) was associated with 1.09 (95% CI = 0.97, 1.22) times higher CRC odds. WHR (per 0.07 higher) was more strongly associated with CRC risk among women (IVW OR = 1.25, 95% CI = 1.08, 1.43) than men (IVW OR = 1.05, 95% CI = 0.81, 1.36). BMI or WHR was associated with 104/123 metabolites at false discovery rate-corrected P ≤ 0.05; several metabolites were associated with CRC, but not in directions that were consistent with the mediation of positive adiposity-CRC relations. In multivariable MR analyses, associations of BMI and WHR with CRC were not attenuated following adjustment for representative metabolite classes, e.g., the univariable IVW OR for BMI with CRC was 1.12 (95% CI = 1.00, 1.26), and this became 1.11 (95% CI = 0.99, 1.26) when adjusting for cholesterol in low-density lipoprotein particles. CONCLUSIONS: Our results suggest that higher BMI more greatly raises CRC risk among men, whereas higher WHR more greatly raises CRC risk among women. Adiposity was associated with numerous metabolic alterations, but none of these explained associations between adiposity and CRC. More detailed metabolomic measures are likely needed to clarify the mechanistic pathways.
Keywords: Waist-to-hip ratio; obezita; celogenomová asociační studie; Sex Factors; NMR; Polymorphism, Single Nucleotide; Humans; Case-Control Studies; Metabolome; index tělesné hmotnosti; lidé středního věku; Body Mass Index; studie případů a kontrol; jednonukleotidový polymorfismus; Female; rizikové faktory; dospělí; mendelovská randomizace; lidé; Epidemiology; Europe; Waist-Hip Ratio; sexuální faktory; Adiposity; metabolom; Adult; Mendelian randomization; ženské pohlaví; Body mass index; kolorektální nádory; Male; Metabolism; Mendelian Randomization Analysis; Middle Aged; Colorectal cancer; Genetic Predisposition to Disease; genetická predispozice k nemoci; CORECT; CCFR; Genome-Wide Association Study; poměr pasu a boků; GECCO; Obesity; mužské pohlaví; adipozita; Evropa; Colorectal Neoplasms; Risk Factors